History of the invasive African olive tree in Australia and Hawaii: evidence for sequential bottlenecks and hybridization with the Mediterranean olive - (:unkn) unknown (My University, 2014)
Humans have introduced plants and animals into new continents and islands with negative effects on local species. This has been the case of the olive that was introduced in Australia, New Zealand and Pacific islands where it became invasive. Two subspecies were introduced in Australia, and each successfully invaded a specific area: the African olive in New South Wales (NSW) and the Mediterranean olive in South Australia. Here, we examine their origins and spread and analyse a large sample of native and invasive accessions with chloroplast and nuclear microsatellites. African olive populations from the invaded range exhibit two South African chlorotypes hence supporting an introduction from South Africa, while populations from South Australia exhibit chlorotypes of Mediterranean cultivars. Congruently, nuclear markers support the occurrence of two lineages in Australia but demonstrate that admixture took place, attesting that they hybridized early after introduction. Furthermore, using an approximate Bayesian computation framework, we found strong support for the serial introduction of the African olive from South Africa to NSW and then from NSW to Hawaii. The taxon experienced successive bottlenecks that did not preclude invasion, meaning that rapid decisions need to be taken to avoid naturalization where it has not established a large population yet.
Keywords: African Research